An Investigation on triaxial compression of flexible fiber packings. Issue 6 (19th February 2020) - Guo, Yu; Li, Yanjie; Liu, Qingzhao; Jin, Hanhui; Xu, Dandan; Wassgren, Carl; Curtis, Jennifer S.
Abstract: This article examines the mechanical response of flexible fiber packings subject to triaxial compression. Short fibers yield in a manner similar to typical granular materials in which the deviatoric stress remains nearly constant with increasing strain after reaching a peak value. Interestingly, long fibers exhibit a hardening behavior, where the stress increases rapidly with increasing strain at large strains and the packing density continuously increases. Phase diagrams for classifying the bulk mechanical response as yielding, hardening, or a transition regime are generated as a function of the fiber aspect ratio and fiber–fiber friction coefficient. Large fiber aspect ratio and large fiber–fiber friction coefficient promote hardening behavior. The positions of boundaries between different regimes depend on the confining pressure and fiber flexibility. The hardening packings can support much larger loads than the yielding packings, but larger internal axial forces within fibers and larger fiber–fiber contact forces occur.